Evaluating the Capacity of a City Development Authority in Bangladesh:: A Qualitative Study - Miti, Sania Sifat; Mahmud, Md. Akter; Kalam, AKM Abul (The Jahangirnagar Review, 2025)
Understanding the capacity of any authority is crucial for determining its ability to fulfill its responsibilities. This research aimed to assess the capacity of RAJUK in serving its jurisdiction effectively. The study gathered insights from key informants on this topic using a qualitative method. A purposeful sampling technique was employed to select academicians, experts, and professionals from the target population. In total, 13 key informants participated in interviews that utilized a semi-structured questionnaire, consisting of both open-ended and closed-ended questions. The findings were analyzed using thematic and narrative analyses with NVivo 14 software. The study revealed a notable lack of capacity in RAJUK to support and monitor development activities within its jurisdiction. Significant concerns regarding RAJUK’s capabilities included issues related to manpower, institutional structure, the number of planners, the extensive size of its jurisdiction, and accountability. To identify similarities among these concerns, a cluster analysis was conducted. The findings of this study contribute to a better understanding of the shortcomings faced by city development authorities and may provide insights for improving their performance. Future research could explore another city development authority in a different urban context to enhance the generalizability of these findings.